Influence of dynamic loads different in duration on changes in the activity of lactate dehydrogenase isoenzymes in intervertebral disc cells - Andrіі Sak; Raisa Antypova (Kharkiv State Academy of Physical Culture, 2020)
Purpose: to determine the effect of prolonged dynamic loads on changes in the activity of lactate dehydrogenase isoenzymes (LDH) in the cells of intervertebral discs in an age-related aspect. Material & methods: the study was performed on male Wistar rats of three age groups: 1, 3, and 12 months. In total, 90 animals of the experimental series and 90 animals of the control series were observed in the experiments. Dynamic loads were created by running in a horizontal treadmill. By the histochemical methods the analysis of changes of activity of lactate dehydrogenase isoenzymes in the cells of intervertebral disks of rats of Vistar line in the conditions of a 20- and 90-day experimental run. Results: changes of activity of lactate dehydrogenase isoenzymes depended on the age of the animal and duration of dynamic loads. A marked decrease in the activity of the intervertebral disc cells the LDH-1 and LDH-2 isoenzymes, but the increasing activity of the LDH-3 and LDH-4 isoenzymes. Conclusions: it is suggested to use the exposed age-dependent features of change activity of enzymes as a histochemycal test for the objective estimation of degree of damaging action of protracted running loadings on a fibrocartilage of the disk.